2022
DOI: 10.3389/fpsyg.2022.916736
|View full text |Cite
|
Sign up to set email alerts
|

Variability in L2 Vowel Production: Different Elicitation Methods Affect Individual Speakers Differently

Abstract: Elicitation methods are known to influence second language speech production. For teachers and language assessors, awareness of such effects is essential to accurate interpretations of testing outcomes. For speech researchers, understanding why one method gives better performance than another may yield insights into how second-language phonological knowledge is acquired, stored, and retrieved. Given these concerns, this investigation compared L2 vowel intelligibility on two elicitation tasks and determined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Firstly, in terms of the elicitation method, the vowels were produced in sentences as responses to precursor questions asked by the experimenter. It has been demonstrated that different elicitation methods will influence how vowels are produced, leading to varying degrees of individual differences [38]. The issue of phonetic accommodation is also worth noting because there is recent evidence that both the L1 and L2 undergo phonetic accommodation [39], so that the L1 and L2 vowels produced in this study may have been affected by the experimenter's vowels.…”
Section: Discussionmentioning
confidence: 80%
“…Firstly, in terms of the elicitation method, the vowels were produced in sentences as responses to precursor questions asked by the experimenter. It has been demonstrated that different elicitation methods will influence how vowels are produced, leading to varying degrees of individual differences [38]. The issue of phonetic accommodation is also worth noting because there is recent evidence that both the L1 and L2 undergo phonetic accommodation [39], so that the L1 and L2 vowels produced in this study may have been affected by the experimenter's vowels.…”
Section: Discussionmentioning
confidence: 80%
“…Processing Laboratory, University of Silesia in Katowice, Poland Phonetic imitation in L2 is gaining interest in second-language speech research(Cao 2023;Chen et al 2023;Jiang & Kennison 2022;Munro 2022;Rojczyk et al 2023). The analysis of the emerging publications reveals that most studies concentrate on adult learners, at the same time largely disregarding younger learners.…”
mentioning
confidence: 99%